Identifikasi Methicillin-Resistant Staphylococcus aureus pada Tenaga Kesehatan di Intensive Care Unit dan Instalasi Gawat Darurat RSU GMIM Pancaran Kasih Manado - Lady Natasha Adelaide; Olivia A. Waworuntu; Fredine E. S. Rares (Jurnal Syntax Admiration, 2025)
Staphylococcus aureus is normal flora colonizing the anterior nares but may become pathogenic when the immune system is compromised. The increase and inappropriate use of antibiotics has resulted in Staphylococcus aureus becoming resistant to methicillin and other β-lactam antibiotics, known as Methicillin-Resistant Staphylococcus aureus (MRSA). MRSA-colonized healthcare workers can be a primary reservoir of MRSA, leading to transmission between healthcare workers and patients.This study aims to identify the presence of MRSA in healthcare workers in the ICU and emergency department of GMIM Pancaran Kasih General Hospital, Manado. Descriptive cross sectional study and total sampling, involving 20 healthcare workers. Nasal swab samples were cultured on MSA media, followed by bacterial identification and sensitivity testing with 30 μg cefoxitin antibiotic discs. A total of 11 samples (55%) of health workers were colonized with Staphylococcus aureus, and 4 samples (20%) were positive for MRSA. The conclusion of this study is that MRSA was found in health workers in the ICU and emergency room of RSU GMIM Pancaran Kasih Manado.